MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN 1-20 MELALUI MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING DENGAN VIDEO COMPACT DISK (VCD) PADA ANAK TUNARUNGU - Zaharah - Isti (Universitas Negeri Padang, 2012)
This research background by problems in the field, that the deaf children in the class D II B SLB Perwari Padang totaling three people can not solve the problem of the sum of numbers 1-20 rows laterally in learning mathematics. The research methodology used was action research (Classroom Action Research). Data on children's ability gained through observation and tests, researchers collaborated with colleagues. Subjects were three deaf children class D II B SLB Perwari Padang. The research process begins with the planning of the activities carried out are: create a lesson plan, make the observation sheet, designing evaluation tools to assess the ability of the child, followed by action, observation, reflection resumed his activities. The research process was conducted in two cycles, namely cycle I and cycle II. Implementation cycle starts from the first and second cycle using a model of creative problem solving learning with video compact disc (VCD) as an aid to the sum of the different forms of the game. The results of the first cycle is considered not optimal then, followed in the second cycle. In the second cycle of the child increases the sum of numbers 1-20 rows laterally through creative problem solving learning model with a video compact disc (VCD) in a game matching the sum of the same in the show on a video compact disc (VCD) with the goal of keeping children more solid in understanding the sum of numbers 1-20 rows laterally. The results of the second cycle children's understanding of numbers 1-20 summation increased with the acquisition of a score value reached 88.8%. Based on these results it can be concluded that the model of learning creative problem solving with a video compact disc (VCD) can be used as an effort to increase the sum of numbers 1-20 series aside for children with hearing impairment.